UNDERSTANDING OF TAX RULES, TAX TARIFFS AND TAX-RIGHTS CONSCIOUSNESS ON e-COMMERCE USERS TAX COMPLIANCE - Rendy, Rendy; Irawati, Wiwit (Universitas Pamulang, 2019)
The purpose of this study was to determine the effect of Understanding Tax Regulations, Tax Rates and Taxpayer Awareness on Taxpayer Compliance with e-Commerce users. The research method used is quantitative research using a questionnaire, this research is distributed to 100 Online Shopping Taxpayers in Depok City. The sample collection technique is Convenience Sampling, data analysis in this study was conducted using data quality test, classic assumption test, multiple regression analysis, t test, F test and test coefficient of determination. The results showed that partially understanding of tax regulations does not affect the compliance of e-Commerce taxpayers, tax rates do not affect the compliance of e-Commerce taxpayers, taxpayer awareness affects e-Commerce users' taxpayer compliance. While simultaneously Understanding Tax Regulations, Tax Rates and Taxpayer Awareness influences the Taxpayer Compliance with e-Commerce users.